Fluorine-free flux for magnesium alloy welding and preparation method thereof
Patent Information
- Application Number
- CN202611211130.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-11
AI Technical Summary
然而,单一氯盐体系仍存在熔化温区较高、活化能力不足以及组分容易偏析等问题,尤其是在焊接初期,部分氯盐尚未形成连续液相,难以及时覆盖镁合金表面,导致氧化膜去除不充分
(1)本发明采用无水氯化钾、无水氯化钠、无水氯化锂、无水氯化钙、无水氯化镁和无水溴化钾组成基础复合盐体系,并加入氯化锌活化锂钙钠复合盐,使镁合金焊接用无氟助焊剂在焊接加热过程中形成含多种卤化物组分的熔融盐环境。无水氯化钾、无水氯化钠、无水氯化锂、无水氯化钙、无水氯化镁和无水溴化钾在受热过程中参与熔融盐相形成,能够调节助焊剂的熔融行为和焊接区域覆盖状态;氯化锌活化锂钙钠复合盐通过将无水氯化锌预先复合于多组分氯化物体系中,使无水氯化锌在助焊剂中的分布状态得到调控,在镁合金焊接过程中,氯化锌活化锂钙钠复合盐能够参与氧化膜与熔融盐之间的界面作用,使镁合金表面氧化膜结构发生变化,促进氧化膜与焊接界面的分离,有利于液态金属在镁合金表面的润湿铺展。
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of magnesium alloy welding materials, specifically relating to a fluorine-free flux for magnesium alloy welding and its preparation method. Background Technology
[0002] Magnesium alloys possess low density, high specific strength, good damping performance, and excellent machinability, making them widely used in aerospace, rail transportation, automotive lightweighting, and electronic equipment structural components. As magnesium alloy components become increasingly larger and more complex, welding, as a crucial processing method for joining magnesium alloy structures, is receiving increasing attention. However, magnesium alloys have high chemical reactivity and readily form a dense oxide film in air. This oxide film, primarily composed of magnesium oxide and small amounts of other oxides, has a high melting point and strong stability. During welding, it is difficult for the oxide film to melt synchronously with the magnesium alloy matrix, easily hindering the wetting and spreading of the molten metal, leading to defects such as incomplete fusion, inclusions, porosity, and unstable weld formation. Simultaneously, the relatively low melting point of magnesium alloys means that excessively high welding heat input can easily cause grain coarsening, hot cracking, and a decline in microstructure and properties. Therefore, flux is needed to reduce the influence of the oxide film and improve the activity of the molten pool and the stability of the welding process. Currently, fluorinated fluxes or fluorinated composite salt systems are often used in magnesium alloy welding to improve welding wettability by utilizing the activation effect of fluorides on the oxide film. However, there are certain environmental control requirements for the production, storage and use of fluorinated components. Fluorinated fumes may be generated during the welding process, and the residues after welding also need to be effectively treated, which is not conducive to the development of green welding technology.
[0003] Existing fluorine-free magnesium alloy fluxes are mainly based on chloride salt systems. These systems use multiple salts such as potassium chloride, sodium chloride, lithium chloride, calcium chloride, and magnesium chloride to lower the melting temperature, allowing the flux to form a coating layer and promote oxide film removal during welding. However, single chloride salt systems still suffer from problems such as high melting temperature range, insufficient activation capacity, and easy component segregation. Especially in the early stages of welding, some chloride salts have not yet formed a continuous liquid phase, making it difficult to cover the magnesium alloy surface in time, resulting in insufficient oxide film removal. Furthermore, existing technologies often directly add active substances such as zinc chloride to enhance oxide film removal capacity. However, the melting behavior of zinc chloride differs significantly from other chloride salts, and direct physical mixing can easily lead to uneven local concentrations, potentially causing problems such as excessively rapid local reactions, uneven residue distribution, and fluctuating flux performance during welding. Meanwhile, some studies use particulate reinforcing materials such as silicon carbide to improve molten pool flow and weld microstructure. However, due to the significant differences in surface properties between silicon carbide particles and chloride salt powders, they are prone to agglomeration and sedimentation during long-term storage and transportation, leading to uneven flux component distribution and affecting the actual welding effect. Therefore, improving the dispersion stability of the active salt component and enhancing the compatibility between the particulate reinforcement component and the base salt system are important issues that need to be addressed in current fluorine-free magnesium alloy welding fluxes. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a fluorine-free flux for welding magnesium alloys, comprising the following components in parts by weight: Anhydrous potassium chloride 22-30 parts, anhydrous sodium chloride 12-18 parts, anhydrous lithium chloride 10-16 parts, anhydrous calcium chloride 8-14 parts, anhydrous magnesium chloride 10-16 parts, anhydrous potassium bromide 3-6 parts, zinc chloride activated lithium calcium sodium composite salt 8-12 parts, magnesium potassium chloride salt coated silicon carbide activated micro powder 3-6 parts.
[0005] According to a preferred embodiment of the present invention, the preparation method of the zinc chloride activated lithium calcium sodium composite salt includes: A1. By weight, 30-38 parts of anhydrous lithium chloride, 26-34 parts of anhydrous calcium chloride and 18-26 parts of anhydrous sodium chloride are vacuum dried separately, and 8-14 parts of anhydrous zinc chloride are vacuum dried; cooled under nitrogen protection; the dried anhydrous lithium chloride, anhydrous calcium chloride, anhydrous sodium chloride and anhydrous zinc chloride are mixed to obtain a composite salt mixture; A2. Add the composite salt mixture to a covered crucible, heat it to 500-530℃ under nitrogen protection, stir and keep it warm to obtain zinc-containing composite molten salt; cool, crush, grind, vibrate and sieve the zinc-containing composite molten salt, and then vacuum dry it.
[0006] In this invention, during the preparation of zinc chloride-activated lithium-calcium-sodium composite salt, anhydrous lithium chloride, anhydrous calcium chloride, anhydrous sodium chloride, and anhydrous zinc chloride are all strongly hygroscopic chlorides. The physically adsorbed water on the surface of the raw materials will cause localized hydrolysis and release hydrogen chloride during subsequent heating. Therefore, vacuum drying is performed first to remove the surface adsorbed water and avoid introducing hydroxyl chloride impurities during the melting stage. After vacuum drying, cooling and mixing under nitrogen protection reduces re-contact with moisture in the air during the mixing stage. When the covered crucible is heated to the set temperature range under nitrogen protection, anhydrous lithium chloride, anhydrous calcium chloride, and anhydrous sodium chloride successively cross their respective liquidus lines corresponding to the system phase diagram, forming a multi-component chloride melt bridged by chloride ions. Each cation migrates in the melt in ionic form. Anhydrous zinc chloride has a melting point below this temperature range and interacts with alkali metal cations and alkaline earth metal cations in the melt as a zinc chloride complex anion. Its activity coefficient with alkali metal chlorides and alkaline earth metal chlorides shows a negative deviation, forming a zinc-containing composite molten salt. The presence of alkali metal chlorides and alkaline earth metal chlorides maintains the activity of anhydrous zinc chloride at a low level, correspondingly reducing the vapor pressure and inhibiting volatilization loss during the heat preservation stage. Stirring and heat preservation make the composition of the zinc-containing composite molten salt more homogeneous. After casting and cooling, the system transforms from a liquid phase into a multiphase coexisting solid condensate. Through crushing, grinding, and vibrating sieving, a zinc chloride-activated lithium calcium sodium composite salt is obtained. The final stage of vacuum drying removes the moisture re-adsorbed during the crushing and grinding stages.
[0007] According to a preferred embodiment of the present invention, in step A1, anhydrous lithium chloride, anhydrous calcium chloride and anhydrous sodium chloride are vacuum dried at 180-230°C for 2-4 hours, and anhydrous zinc chloride is vacuum dried at 120-160°C for 1.5-3 hours.
[0008] According to a preferred embodiment of the present invention, in step A2, the stirring and heat preservation time is 20-40 minutes at 500-530°C.
[0009] According to a preferred embodiment of the present invention, the method for preparing the magnesium potassium chloride-coated silicon carbide activated micro powder includes: B1. By weight, 45-55 parts of anhydrous magnesium chloride and 25-35 parts of anhydrous potassium chloride are vacuum dried separately, and 15-25 parts of green silicon carbide micro powder are vacuum dried and cooled under nitrogen protection; the dried anhydrous magnesium chloride and anhydrous potassium chloride are added to a covered crucible, heated to 500-550℃ under nitrogen protection, stirred and kept at the temperature to obtain magnesium potassium chloride composite molten salt; B2. Under stirring, the dried green silicon carbide micro powder is added to the magnesium potassium chloride composite molten salt, and stirring is continued to obtain the coated molten salt slurry; the coated molten salt slurry is cooled, crushed, ground, vibrated and screened, and then vacuum dried.
[0010] In this invention, during the preparation of magnesium-potassium chloride-coated activated silicon carbide micropowder, anhydrous magnesium chloride, being a strongly hygroscopic chloride, hydrolyzes to form basic magnesium chloride and hydrogen chloride at temperatures exceeding a certain threshold. Therefore, it is first vacuum-dried to remove surface adsorbed water, preventing the introduction of magnesium oxide and basic magnesium chloride impurities into the molten salt phase. Anhydrous potassium chloride and green silicon carbide micropowder are simultaneously dried to reduce the impact of surface adsorbed moisture on the subsequent molten salt adhesion process. Under nitrogen protection, anhydrous magnesium chloride and anhydrous potassium chloride are heated above the liquidus line corresponding to the magnesium-potassium chloride system phase diagram. The two are mixed in a specific ratio to form a magnesium-potassium chloride composite molten salt bridged by chloride ions. The melt simultaneously contains potassium cations, magnesium cations, and chloride-bridged magnesium chloride complex anions, exhibiting continuous liquid-phase fluidity. Green silicon carbide micropowder does not participate in the displacement reaction in dry chloride molten salt without metallic magnesium or strong reducing agents, and is added as an inert solid particle to magnesium-potassium chloride composite molten salt. Under stirring conditions, the liquid-phase magnesium-potassium chloride composite molten salt wets the surface of the green silicon carbide micropowder through capillary force and interfacial tension, forming a slurry-like dispersion in which the liquid phase covers the solid particles, i.e., coated molten salt slurry. During the slurry casting and cooling process, the liquid-phase magnesium-potassium chloride composite molten salt solidifies into a solid chloride layer covering the surface of the green silicon carbide micropowder. After crushing, grinding, and vibrating sieving, magnesium-potassium chloride coated activated silicon carbide micropowder is obtained. The chloride solidification layer physically isolates the green silicon carbide micropowder from external moisture and also improves the compatibility between the green silicon carbide micropowder and the basic fluorine-free composite salt in subsequent mixing processes.
[0011] According to a preferred embodiment of the present invention, in step B1, the stirring and heat preservation time is 20-40 minutes.
[0012] According to a preferred embodiment of the present invention, in step B2, the dried green silicon carbide micro powder is added to the magnesium potassium chloride composite molten salt, and the stirring time is continued for 20-40 minutes.
[0013] The present invention also provides a method for preparing the aforementioned fluorine-free flux for welding magnesium alloys, comprising the following steps: S1. Dry anhydrous potassium chloride, anhydrous sodium chloride, and anhydrous potassium bromide. Vacuum dry anhydrous lithium chloride, anhydrous calcium chloride, and anhydrous magnesium chloride. After drying, cool under nitrogen protection. Mix the dried anhydrous potassium chloride, anhydrous sodium chloride, anhydrous lithium chloride, anhydrous calcium chloride, anhydrous magnesium chloride, and anhydrous potassium bromide to obtain a basic fluorine-free composite salt. S2. Under stirring, zinc chloride activated lithium calcium sodium composite salt and magnesium potassium chloride salt coated silicon carbide activated micro powder are added to the basic fluorine-free composite salt in sequence and mixed further to obtain flux mixed powder; the flux mixed powder is deagglomerated and vibrated sieve, then vacuum dried and sealed in packaging.
[0014] In this invention, during the preparation of the fluorine-free flux for magnesium alloy welding, anhydrous potassium chloride, anhydrous sodium chloride, and anhydrous potassium bromide are conventional hygroscopic halides, and their surface moisture can be removed by conventional drying. Anhydrous lithium chloride, anhydrous calcium chloride, and anhydrous magnesium chloride have significantly stronger hygroscopicity; therefore, vacuum drying is used, and the temperature is controlled below their hydrolysis initiation temperature to avoid the formation of hydroxyl chlorides and oxide inclusions during the heating stage. The above six halides form a basic fluorine-free composite salt under closed mixing conditions. The components together cover a wide melting temperature range, serving as the skeleton components for the slag layer formed during welding. Zinc chloride activated lithium calcium sodium composite salt and magnesium potassium chloride salt-coated silicon carbide activated micropowder are sequentially added to the basic fluorine-free composite salt to obtain a flux mixed powder, which is then depolymerized, vibrated, sieved, vacuum dried, and sealed in packaging. During welding, the flux melts upon heating, forming a continuous molten salt coating in the welding area. This coating isolates the welding area from the air, inhibiting the continuous oxidation of the magnesium alloy surface. Chloride and bromide ions in the molten salt penetrate and complex with the magnesium oxide surface, loosening the oxide film structure and causing it to detach and migrate from the welding interface to the slag phase. The zinc chloride complex anions contributed by the zinc chloride-activated lithium calcium sodium composite salt have a stronger chemical affinity for oxides, further promoting the destruction and transfer of the oxide film. At the high welding temperature, the outer chloride layer of the magnesium potassium chloride-coated activated silicon carbide powder melts and releases, dispersing the green silicon carbide powder into the slag area and participating in regulating the local heat transfer behavior of the weld pool. These effects collectively constitute the fluxing process under fluorine-free conditions.
[0015] According to a preferred embodiment of the present invention, in step S1, anhydrous potassium chloride, anhydrous sodium chloride and anhydrous potassium bromide are dried at 180-220°C for 2-3 hours, and anhydrous lithium chloride, anhydrous calcium chloride and anhydrous magnesium chloride are vacuum dried at 140-170°C for 3-5 hours.
[0016] According to a preferred embodiment of the present invention, in step S2, the temperature of vacuum drying is 120-150°C, and the time of vacuum drying is 1-2 hours.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention uses anhydrous potassium chloride, anhydrous sodium chloride, anhydrous lithium chloride, anhydrous calcium chloride, anhydrous magnesium chloride, and anhydrous potassium bromide to form a basic composite salt system, and adds zinc chloride activated lithium calcium sodium composite salt to form a molten salt environment containing multiple halide components in the welding heating process of the fluorine-free flux for magnesium alloy welding. Anhydrous potassium chloride, anhydrous sodium chloride, anhydrous lithium chloride, anhydrous calcium chloride, anhydrous magnesium chloride, and anhydrous potassium bromide participate in the formation of molten salt phase during heating, which can regulate the melting behavior of flux and the coverage state of welding area; the zinc chloride activated lithium calcium sodium composite salt regulates the distribution state of anhydrous zinc chloride in flux by pre-composite anhydrous zinc chloride in the multi-component chloride system. In the magnesium alloy welding process, the zinc chloride activated lithium calcium sodium composite salt can participate in the interfacial interaction between oxide film and molten salt, causing changes in the oxide film structure on the magnesium alloy surface, promoting the separation of oxide film and welding interface, and facilitating the wetting and spreading of liquid metal on the magnesium alloy surface.
[0018] (2) This invention uses magnesium potassium chloride-coated activated silicon carbide micropowder as a particle control component. Anhydrous magnesium chloride and anhydrous potassium chloride form a magnesium potassium chloride composite molten salt, which is then used to coat the green silicon carbide micropowder, allowing it to exist in a coated state within the flux system. The magnesium potassium chloride composite molten salt in the magnesium potassium chloride-coated activated silicon carbide micropowder melts at the welding temperature, allowing the green silicon carbide micropowder to enter the welding zone. As solid particles, the green silicon carbide micropowder participates in the heat transfer and solidification processes of the molten pool in the welding zone, influencing the formation of the weld zone microstructure. By using magnesium potassium chloride-coated activated silicon carbide micropowder, a relatively uniform particle distribution is maintained during flux mixing, reducing the particle aggregation that may occur when the green silicon carbide micropowder is directly added to a multi-component salt system.
[0019] (3) This invention forms a fluorine-free flux system for magnesium alloy welding through the compounding effect of zinc chloride-activated lithium calcium sodium composite salt, magnesium potassium chloride-coated silicon carbide activated micro powder, anhydrous potassium chloride, anhydrous sodium chloride, anhydrous lithium chloride, anhydrous calcium chloride, anhydrous magnesium chloride, and anhydrous potassium bromide. During the welding process, the fluorine-free flux for magnesium alloy welding forms a molten salt coating layer when heated, reducing the degree of direct contact between the welding area and air, and reducing further oxidation of the magnesium alloy surface; the zinc chloride-activated lithium calcium sodium composite salt participates in the oxide film interface activation process, promoting the interaction between the oxide film and the molten salt phase; the green silicon carbide micro powder in the magnesium potassium chloride-coated silicon carbide activated micro powder enters the action area during the welding process, and plays a regulatory role in the state of the molten pool and the solidification process. This invention does not use fluoride-containing salts as active components. The anhydrous potassium chloride, anhydrous sodium chloride, anhydrous lithium chloride, anhydrous calcium chloride, anhydrous magnesium chloride, anhydrous potassium bromide, anhydrous zinc chloride, and green silicon carbide micro powder used are all commonly used industrial raw materials. The preparation process includes drying, melt compounding, cooling treatment, crushing and sieving, and mixing treatment to form a fluoride-free flux suitable for the auxiliary process of magnesium alloy welding. Detailed Implementation
[0020] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0021] Example 1 This embodiment provides a method for preparing a fluorine-free flux for magnesium alloy welding, the steps of which include: S1. Weigh 26g of anhydrous potassium chloride, 15g of anhydrous sodium chloride, 13g of anhydrous lithium chloride, 11g of anhydrous calcium chloride, 13g of anhydrous magnesium chloride, and 4.5g of anhydrous potassium bromide. Spread the anhydrous potassium chloride, anhydrous sodium chloride, and anhydrous potassium bromide separately in a drying container and dry at 200℃ for 2.5h. Spread the anhydrous lithium chloride, anhydrous calcium chloride, and anhydrous magnesium chloride separately in a vacuum drying container and vacuum dry at 155℃ and 5kPa absolute pressure for 4h, controlling the thickness of each material layer to 10mm. After drying, add the anhydrous potassium chloride... Anhydrous sodium chloride and anhydrous potassium bromide were transferred to a nitrogen-protected container. Anhydrous lithium chloride, anhydrous calcium chloride, and anhydrous magnesium chloride were purged with nitrogen to remove the vacuum and then transferred to a nitrogen-protected container. All materials were cooled to 25°C under nitrogen flow rate of 200 mL / min. The dried anhydrous potassium chloride, anhydrous sodium chloride, anhydrous lithium chloride, anhydrous calcium chloride, anhydrous magnesium chloride, and anhydrous potassium bromide were added to a closed mixing device and mixed for 30 min under nitrogen flow rate of 200 mL / min and rotation speed of 60 r / min to obtain the basic fluorine-free composite salt. S2. Weigh 10g of zinc chloride activated lithium calcium sodium composite salt and 4.5g of magnesium potassium chloride salt-coated silicon carbide activated micro powder. Maintain the basic fluorine-free composite salt under nitrogen flow rate of 200mL / min and stirring speed of 60r / min. Add 10g of zinc chloride activated lithium calcium sodium composite salt to the basic fluorine-free composite salt within 5min, continue mixing for 20min, then add 4.5g of magnesium potassium chloride salt-coated silicon carbide activated micro powder within 5min, continue mixing for 20min to obtain flux mixed powder. Place the flux mixed powder in a... In a closed depolymerization device, the material is depolymerized at 2000 r / min for 3 min, and then sieved through a vibrating screen with a sieve aperture of 100 μm to collect the undersized powder. The undersized powder is spread evenly in a drying container with a material layer thickness controlled at 10 mm, and vacuum dried at 135℃ and 5 kPa absolute pressure for 1.5 h. Nitrogen gas is introduced to release the vacuum, and the material is cooled to no higher than 40℃ under nitrogen protection. The material is then sealed and packaged under an ambient temperature of 25℃ and a relative humidity of no higher than 20% to obtain a fluorine-free flux for magnesium alloy welding.
[0022] Preparation steps of zinc chloride activated lithium calcium sodium complex salt: A1. Weigh 34g of anhydrous lithium chloride, 30g of anhydrous calcium chloride, 22g of anhydrous sodium chloride, and 11g of anhydrous zinc chloride. Spread the anhydrous lithium chloride, calcium chloride, and sodium chloride separately in a drying container, maintaining a layer thickness of 10mm. Vacuum dry each at 205℃ and 5kPa for 3 hours. Spread the anhydrous zinc chloride in another drying container, maintaining a layer thickness of 10mm, and vacuum dry at 140℃ and 5kPa for 2.25 hours. After drying, nitrogen gas is introduced into the vacuum drying equipment to release the vacuum. The dried anhydrous lithium chloride, anhydrous calcium chloride, anhydrous sodium chloride, and anhydrous zinc chloride are then transferred to a nitrogen-protected container and cooled to 25°C under a nitrogen flow rate of 200 mL / min. The cooled anhydrous lithium chloride, anhydrous calcium chloride, anhydrous sodium chloride, and anhydrous zinc chloride are then added to a closed mixing device and mixed for 30 min under a nitrogen flow rate of 200 mL / min and a rotation speed of 60 r / min to obtain a composite salt mixture. A2. Add the composite salt mixture obtained in step A1 to a high-purity graphite crucible with a lid. The volume of the composite salt mixture should not exceed 70% of the effective volume of the high-purity graphite crucible with a lid. Cover the high-purity graphite crucible with a lid and purge the internal air with nitrogen gas at a flow rate of 300 mL / min for 20 min. Then, maintain the nitrogen flow rate at 200 mL / min and heat to 515℃ at a heating rate of 5℃ / min. After the material has completely formed a continuous liquid molten salt, stir it with a high-purity graphite stirring rod at 200 r / min and hold it at 515℃ for 30 min to obtain a zinc-containing composite molten salt. After the holding period, pour the zinc-containing composite molten salt into a pre-dried high-purity graphite cooling pan, controlling the zinc content... The zinc composite molten salt was spread to a thickness of 1.0 mm and cooled to below 80°C under nitrogen flow rate of 200 mL / min, and then cooled to 25°C in a sealed environment. The solidified zinc composite molten salt was crushed to a particle size of no more than 5 mm and placed in a sealed pulverizing device to be pulverized at 3000 r / min for 5 min. It was then sieved through a vibrating screen with a sieve aperture of 100 μm and the undersize powder was collected. The undersize powder was spread evenly in a drying container with a material layer thickness controlled at 10 mm and vacuum dried at 135°C and an absolute pressure of 5 kPa for 1.5 h. Nitrogen was introduced to release the vacuum, and the mixture was cooled to 25°C under nitrogen protection to obtain zinc chloride activated lithium calcium sodium composite salt, which was immediately placed in a sealed container for later use.
[0023] Preparation steps of magnesium potassium chloride-coated activated silicon carbide micro powder: B1. Weigh 50g of anhydrous magnesium chloride, 30g of anhydrous potassium chloride, and 20g of green silicon carbide micro powder. Spread the anhydrous magnesium chloride evenly in a drying container and vacuum dry at 155℃ and 5kPa absolute pressure for 4 hours. Spread the anhydrous potassium chloride evenly in another drying container and vacuum dry at 200℃ and 5kPa absolute pressure for 2.5 hours. Spread the green silicon carbide micro powder evenly in another drying container and vacuum dry at 135℃ and 5kPa absolute pressure for 2 hours. The thickness of each material layer should be controlled to 10mm. After drying, nitrogen gas is introduced to release the vacuum at a nitrogen flow rate of 200mL / min. The mixture was cooled to 25°C. The dried anhydrous magnesium chloride and anhydrous potassium chloride were added to a 500mL high-purity graphite crucible with a lid, the filling volume not exceeding 70% of the effective volume of the crucible. After sealing, nitrogen gas was introduced at a flow rate of 300mL / min for 20min, and then the nitrogen flow rate was maintained at 200mL / min. The temperature was increased to 525°C at a rate of 5°C / min. After the anhydrous magnesium chloride and anhydrous potassium chloride formed a continuous liquid molten salt, the mixture was stirred at 200r / min using a high-purity graphite stirring rod and held at 525°C for 30min to obtain a magnesium-potassium chloride composite molten salt. B2. Maintaining the temperature of the magnesium-potassium-chloride composite molten salt at 525℃, the nitrogen flow rate at 200mL / min, and the stirring speed at 200r / min, divide 20g of dried green silicon carbide micropowder into 5 batches. Add each batch to the magnesium-potassium-chloride composite molten salt within 2min, with a 2min interval between adjacent batches. The total addition time for the green silicon carbide micropowder is 18min. After all the green silicon carbide micropowder has been added, continue stirring for 30min at 525℃ and 200r / min to obtain a coated molten salt slurry. Pour the coated molten salt slurry into a pre-dried high-purity graphite cooling pan, controlling the spreading thickness to 1.0mm, and then stir under a nitrogen flow. Cool the material to below 80℃ at a flow rate of 200 mL / min, then cool it to 25℃ in a sealed environment. Crush the solidified coated molten salt slurry to a particle size of no more than 5 mm, and crush it at 3000 r / min for 5 min in a sealed pulverizer. Then, sieve it through a vibrating screen with a sieve aperture of 100 μm and collect the undersize powder. Spread the undersize powder evenly in a drying container with a material layer thickness of 10 mm, and vacuum dry it at 135℃ and an absolute pressure of 5 kPa for 1.5 h. Release the vacuum by introducing nitrogen gas, and cool it to 25℃ under nitrogen protection to obtain magnesium potassium chloride-coated silicon carbide activated micro powder, which is immediately placed in a sealed container for later use.
[0024] Example 2 The difference between this embodiment and Embodiment 1 is that this embodiment provides a method for preparing a fluorine-free flux for magnesium alloy welding, the steps of which include: S1. Weigh 22g of anhydrous potassium chloride, 12g of anhydrous sodium chloride, 10g of anhydrous lithium chloride, 8g of anhydrous calcium chloride, 10g of anhydrous magnesium chloride, and 3g of anhydrous potassium bromide. Dry the anhydrous potassium chloride, anhydrous sodium chloride, and anhydrous potassium bromide at 180℃ for 2 hours. Vacuum dry the anhydrous lithium chloride, anhydrous calcium chloride, and anhydrous magnesium chloride at 140℃ and an absolute pressure of 5kPa for 3 hours, controlling the thickness of each material layer to be 10mm. After drying, cool to 25℃ under a nitrogen flow rate of 200mL / min. Add all materials to a closed mixing device and mix for 30 minutes under a nitrogen flow rate of 200mL / min and a rotation speed of 60r / min to obtain the basic fluorine-free composite salt. S2. Weigh 8g of zinc chloride activated lithium calcium sodium composite salt and 3g of magnesium potassium chloride salt-coated silicon carbide activated micro powder. Under the conditions of nitrogen flow rate of 200mL / min and rotation speed of 60r / min, add 8g of zinc chloride activated lithium calcium sodium composite salt to the basic fluorine-free composite salt within 5min, and continue mixing for 20min. Then add 3g of magnesium potassium chloride salt-coated silicon carbide activated micro powder within 5min, and continue mixing for 20min. Depolymerize the resulting flux mixture powder at 2000r / min for 3min, and sieve it through a vibrating screen with a sieve size of 100μm. Vacuum dry the sieved powder at 120℃ and absolute pressure of 5kPa for 1h. Release the vacuum by purging nitrogen, cool it to no higher than 40℃ under nitrogen protection, and seal and package it under the conditions of ambient temperature of 25℃ and relative humidity of no higher than 20% to obtain fluorine-free flux for magnesium alloy welding.
[0025] Preparation steps of zinc chloride activated lithium calcium sodium complex salt: A1. Weigh 30g of anhydrous lithium chloride, 26g of anhydrous calcium chloride, 18g of anhydrous sodium chloride, and 8g of anhydrous zinc chloride. Spread the anhydrous lithium chloride, anhydrous calcium chloride, and anhydrous sodium chloride separately in a drying container, controlling the material layer thickness to 10mm. Vacuum dry them separately at 180℃ and 5kPa absolute pressure for 2h. Spread the anhydrous zinc chloride in another drying container and vacuum dry it at 120℃ and 5kPa absolute pressure for 1.5h. After drying, purge with nitrogen to release the vacuum, transfer each material to a nitrogen-protected container, and cool it to 25℃ at a nitrogen flow rate of 200mL / min. Add the dried anhydrous lithium chloride, anhydrous calcium chloride, anhydrous sodium chloride, and anhydrous zinc chloride to a closed mixing device and mix for 30min at a nitrogen flow rate of 200mL / min and a rotation speed of 60r / min to obtain a composite salt mixture. A2. Add the composite salt mixture to a high-purity graphite crucible with a lid, filling the crucible to no more than 70% of its effective volume. Purge with nitrogen gas at a flow rate of 300 mL / min for 20 min, then maintain the nitrogen flow rate at 200 mL / min and heat to 500℃ at a rate of 5℃ / min. Stir with a high-purity graphite stirring rod at 200 r / min and hold at 500℃ for 20 min to obtain a zinc-containing composite molten salt. Pour the zinc-containing composite molten salt into a pre-dried high-purity graphite cooling pan. The spreading thickness was controlled to 1.0 mm. The mixture was cooled to below 80°C under nitrogen flow rate of 200 mL / min, and then cooled to 25°C in a sealed environment. The solidified material was crushed to a particle size of no more than 5 mm and pulverized at 3000 r / min for 5 min in a sealed pulverizing device. The powder was then sieved through a vibrating screen with a sieve aperture of 100 μm. The undersized powder was vacuum dried at 120°C and 5 kPa absolute pressure for 1 h. Nitrogen gas was introduced to release the vacuum and the mixture was cooled to 25°C to obtain zinc chloride activated lithium calcium sodium composite salt.
[0026] Preparation steps of magnesium potassium chloride-coated activated silicon carbide micro powder: B1. Weigh 45g of anhydrous magnesium chloride, 25g of anhydrous potassium chloride, and 15g of green silicon carbide micro powder. Vacuum dry the anhydrous magnesium chloride at 140℃ and 5kPa absolute pressure for 3h, vacuum dry the anhydrous potassium chloride at 180℃ and 5kPa absolute pressure for 2h, and vacuum dry the green silicon carbide micro powder at 120℃ and 5kPa absolute pressure for 1h. The thickness of each material layer is controlled to be 10mm. After drying, nitrogen gas is introduced to release the vacuum, and the mixture is cooled to 25℃ at a nitrogen flow rate of 200mL / min. Add the anhydrous magnesium chloride and anhydrous potassium chloride to a high-purity graphite crucible with a lid, introduce nitrogen gas at a flow rate of 300mL / min for 20min, and then maintain the nitrogen flow rate at 200mL / min. Heat the mixture to 500℃ at a heating rate of 5℃ / min, stir it with a high-purity graphite stirring rod at 200r / min, and hold it at 500℃ for 20min to obtain a magnesium-potassium chloride composite molten salt. B2. Maintain the temperature of the magnesium-potassium chloride composite molten salt at 500℃, the nitrogen flow rate at 200mL / min, and the stirring speed at 200r / min. Divide 15g of dried green silicon carbide micro powder into 5 batches, adding each batch within 2min, with a 2min interval between adjacent batches. After all batches are added, continue stirring for 20min to obtain the coated molten salt slurry. Pour the coated molten salt slurry into a high-purity graphite cooling pan, controlling the spreading thickness to 1.0mm. Cool to below 80℃ under nitrogen protection, and then cool to 25℃ in a sealed environment. Crush the solidified material to a particle size of no more than 5mm, and crush it at 3000r / min for 5min in a closed pulverizer. Sieve it through a vibrating screen with a sieve aperture of 100μm. Vacuum dry the undersized powder at 120℃ and an absolute pressure of 5kPa for 1h. Purge with nitrogen to release the vacuum and cool to 25℃ to obtain magnesium-potassium chloride coated silicon carbide activated micro powder.
[0027] Example 3 The difference between this embodiment and Embodiment 1 is that this embodiment provides a method for preparing a fluorine-free flux for magnesium alloy welding, the steps of which include: S1. Weigh 30g of anhydrous potassium chloride, 18g of anhydrous sodium chloride, 16g of anhydrous lithium chloride, 14g of anhydrous calcium chloride, 16g of anhydrous magnesium chloride, and 6g of anhydrous potassium bromide. Dry the anhydrous potassium chloride, anhydrous sodium chloride, and anhydrous potassium bromide at 220℃ for 3 hours. Vacuum dry the anhydrous lithium chloride, anhydrous calcium chloride, and anhydrous magnesium chloride at 170℃ and an absolute pressure of 5kPa for 5 hours, controlling the thickness of each material layer to be 10mm. After drying, cool to 25℃ under nitrogen flow rate of 200mL / min. Add all materials to a closed mixing device and mix for 30 minutes under nitrogen flow rate of 200mL / min and rotation speed of 60r / min to obtain the basic fluorine-free composite salt. S2. Weigh 12g of zinc chloride activated lithium calcium sodium composite salt and 6g of magnesium potassium chloride salt-coated silicon carbide activated micro powder. Under the conditions of nitrogen flow rate of 200mL / min and rotation speed of 60r / min, add 12g of zinc chloride activated lithium calcium sodium composite salt to the basic fluorine-free composite salt within 5min and continue mixing for 20min. Then add 6g of magnesium potassium chloride salt-coated silicon carbide activated micro powder within 5min and continue mixing for 20min. Depolymerize the resulting flux mixture powder at 2000r / min for 3min, sieve it through a vibrating screen with a sieve size of 100μm, and vacuum dry the sieved powder at 150℃ and absolute pressure of 5kPa for 2h. Release the vacuum by purging nitrogen and cool it to no higher than 40℃ under nitrogen protection. Seal and package it under the conditions of ambient temperature of 25℃ and relative humidity of no higher than 20% to obtain fluorine-free flux for magnesium alloy welding.
[0028] Preparation steps of zinc chloride activated lithium calcium sodium complex salt: A1. Weigh 38g of anhydrous lithium chloride, 34g of anhydrous calcium chloride, 26g of anhydrous sodium chloride, and 14g of anhydrous zinc chloride. Spread the anhydrous lithium chloride, anhydrous calcium chloride, and anhydrous sodium chloride separately in drying containers, with the material layer thickness controlled at 10mm. Vacuum dry them separately at 230℃ and 5kPa absolute pressure for 4h. Spread the anhydrous zinc chloride in another drying container and vacuum dry it at 160℃ and 5kPa absolute pressure for 3h. After drying, purge with nitrogen to release the vacuum and transfer each material to a nitrogen-protected container. Cool it to 25℃ at a nitrogen flow rate of 200mL / min. Add the dried anhydrous lithium chloride, anhydrous calcium chloride, anhydrous sodium chloride, and anhydrous zinc chloride to a closed mixing device and mix for 30min at a nitrogen flow rate of 200mL / min and a rotation speed of 60r / min to obtain a composite salt mixture. A2. Add the composite salt mixture to a high-purity graphite crucible with a lid, filling the crucible to no more than 70% of its effective volume. Purge with nitrogen gas at a flow rate of 300 mL / min for 20 min, then maintain the nitrogen flow rate at 200 mL / min and heat to 530°C at a rate of 5°C / min. Stir with a high-purity graphite stirring rod at 200 r / min and hold at 530°C for 40 min to obtain a zinc-containing composite molten salt. Pour the zinc-containing composite molten salt into a pre-dried high-purity graphite cooling pan. The spreading thickness was controlled at 1.0 mm. The mixture was cooled to below 80°C under nitrogen flow rate of 200 mL / min, and then cooled to 25°C in a sealed environment. The solidified material was crushed to a particle size of no more than 5 mm and pulverized at 3000 r / min for 5 min in a sealed pulverizing device. The powder was then sieved through a vibrating screen with a sieve aperture of 100 μm. The undersized powder was vacuum dried at 150°C and 5 kPa absolute pressure for 2 h. Nitrogen gas was introduced to release the vacuum and the mixture was cooled to 25°C to obtain zinc chloride activated lithium calcium sodium composite salt.
[0029] Preparation steps of magnesium potassium chloride-coated activated silicon carbide micro powder: B1. Weigh 55g of anhydrous magnesium chloride, 35g of anhydrous potassium chloride, and 25g of green silicon carbide micro powder. Vacuum dry the anhydrous magnesium chloride at 170℃ and 5kPa absolute pressure for 5h, vacuum dry the anhydrous potassium chloride at 220℃ and 5kPa absolute pressure for 3h, and vacuum dry the green silicon carbide micro powder at 150℃ and 5kPa absolute pressure for 3h. The thickness of each material layer is controlled to be 10mm. After drying, nitrogen gas is introduced to release the vacuum, and the mixture is cooled to 25℃ at a nitrogen flow rate of 200mL / min. Add the anhydrous magnesium chloride and anhydrous potassium chloride to a high-purity graphite crucible with a lid, introduce nitrogen gas at a flow rate of 300mL / min for 20min, and then maintain the nitrogen flow rate at 200mL / min. Heat the mixture to 550℃ at a heating rate of 5℃ / min, stir with a high-purity graphite stirring rod at 200r / min, and hold at 550℃ for 40min to obtain a magnesium-potassium chloride composite molten salt. B2. Maintain the temperature of the magnesium-potassium chloride composite molten salt at 550℃, the nitrogen flow rate at 200mL / min, and the stirring speed at 200r / min. Divide 25g of dried green silicon carbide micro powder into 5 batches, adding each batch within 2min, with a 2min interval between adjacent batches. After all batches are added, continue stirring for 40min to obtain the coated molten salt slurry. Pour the coated molten salt slurry into a high-purity graphite cooling pan, controlling the spreading thickness to 1.0mm. Cool to below 80℃ under nitrogen protection, and then cool to 25℃ in a sealed environment. Crush the solidified material to a particle size of no more than 5mm, and crush it at 3000r / min for 5min in a sealed pulverizer. Sieve it through a vibrating screen with a sieve aperture of 100μm. Vacuum dry the undersized powder at 150℃ and an absolute pressure of 5kPa for 2h. Release the vacuum by introducing nitrogen and cool to 25℃ to obtain magnesium-potassium chloride coated silicon carbide activated micro powder.
[0030] Comparative Example 1 The difference between this comparative example and Example 1 is that the zinc chloride activated lithium calcium sodium complex salt is not used. Instead, 10g of the zinc chloride activated lithium calcium sodium complex salt is replaced with a chloride salt mixture formed by directly mixing 3.51g of anhydrous lithium chloride, 3.09g of anhydrous calcium chloride, 2.27g of anhydrous sodium chloride and 1.13g of anhydrous zinc chloride. The rest is the same as in Example 1.
[0031] Comparative Example 2 The difference between this comparative example and Example 1 is that magnesium potassium chloride salt coated silicon carbide activated micro powder is not used. Instead, 4.5g of magnesium potassium chloride salt coated silicon carbide activated micro powder is replaced with a mixture formed by directly mixing 2.25g of anhydrous magnesium chloride, 1.35g of anhydrous potassium chloride and 0.90g of green silicon carbide micro powder. The rest is the same as in Example 1.
[0032] Comparative Example 3 The difference between this comparative example and Example 1 is that the zinc chloride-activated lithium calcium sodium complex salt and magnesium potassium chloride salt coated silicon carbide activated micro powder are not used. Instead, 10g of zinc chloride-activated lithium calcium sodium complex salt is replaced with a chloride salt mixture formed by directly mixing 3.51g of anhydrous lithium chloride, 3.09g of anhydrous calcium chloride, 2.27g of anhydrous sodium chloride and 1.13g of anhydrous zinc chloride. The 4.5g of magnesium potassium chloride salt coated silicon carbide activated micro powder is replaced with a mixture formed by directly mixing 2.25g of anhydrous magnesium chloride, 1.35g of anhydrous potassium chloride and 0.90g of green silicon carbide micro powder. The rest is the same as in Example 1.
[0033] The performance of the fluorine-free fluxes for magnesium alloy welding obtained in Examples 1-3 and Comparative Examples 1-3 was tested.
[0034] The fluorine-free fluxes for magnesium alloy welding prepared in Examples 1, 2, 3, 1, 2, and 3 were used as test samples. All test samples were taken immediately after the sealed packaging was opened. For the moisture test, three 0.500g test samples were weighed in parallel for each group. The test samples were quickly added to a sealed titration cup containing a mixture of anhydrous methanol and formamide. The chloride salt components were fully dissolved or dispersed under continuous stirring. The moisture content was determined by the Karl Fischer method. The mass fraction of moisture in the test sample was calculated based on the amount of Karl Fischer reagent consumed. The arithmetic mean of the three parallel determinations was taken as the moisture test result.
[0035] For the total fluoride content test, three 1.000g test samples were weighed in parallel for each group and added to polyethylene beakers. 50mL of deionized water was added, and the mixture was stirred at 25℃ for 30min to fully dissolve the soluble salt components. The samples were filtered to remove insoluble substances such as green silicon carbide powder. The filtrate was brought to a final volume of 100mL. An appropriate amount of the filtrate was transferred and an equal volume of total ionic strength adjustment buffer was added. The fluoride ion selective electrode was used for the determination. A calibration relationship between potential and fluoride ion concentration was established using a series of fluoride standard solutions. The total fluoride content was calculated based on the measured concentration, final volume, and sample mass. The arithmetic mean of the three parallel determinations was taken. If the result was lower than the method detection limit, it was recorded as not detected.
[0036] Welding tests were conducted using AZ31B magnesium alloy plates that met the requirements for magnesium and magnesium alloy sheets. For penetration depth and aspect ratio tests, flat samples measuring 150mm × 75mm × 6mm were used. Five test plates were prepared for each flux. The surfaces of the test plates to be welded were sequentially sanded vertically with 400-grit and 600-grit sandpaper to remove the loose oxide film. After cleaning with anhydrous ethanol and drying, the test sample was mixed with anhydrous ethanol at a 1:1 mass ratio and stirred to form a uniform slurry. This slurry was then evenly applied to a 6mm area on both sides of the center line of the test plate, with the amount of dry flux applied controlled at 3.0 mg / cm². 2The plates were dried at 80℃ for 15 minutes and then subjected to single-pass autofusion welding using AC tungsten inert gas (TIG) welding. The TIG diameter was 3.2 mm, the distance from the TIG tip to the test plate surface was 2.0 mm, the welding current was 120 A, the arc voltage was 13 V, the welding speed was 150 mm / min, the argon purity was not less than 99.99%, the front shielding gas flow rate was 15 L / min, and the weld length was 100 mm. All test plates were welded using the same equipment, clamping conditions, and welding parameters. Macroscopic inspection of the weld was performed by examining the center of the weld along the length of each plate sample. Five samples were obtained by taking one cross-section from each section. The cross-sections were subjected to rough grinding, fine grinding, polishing and etching treatment in sequence. Complete weld cross-section images were obtained under a stereomicroscope. The weld penetration depth was defined as the vertical distance from the original outline of the upper surface of the test plate to the deepest fusion position of the weld. The weld width was defined as the horizontal distance between the fusion boundaries on both sides of the upper surface of the weld cross-section. The weld penetration depth and weld width were measured using calibrated image measurement software. The ratio of weld penetration depth to weld width was calculated. The arithmetic mean of the test results of the five cross-sections was taken as the weld penetration depth and the ratio of weld penetration depth to weld width test results.
[0037] Porosity and transverse tensile strength were tested using AZ31B magnesium alloy plates measuring 200mm × 100mm × 3mm. Two plates were butt-welded along a 200mm direction using a non-bevel butt joint with a 0.5mm gap and a misalignment not exceeding 0.2mm. Surface treatment and flux application were performed on 6mm areas on both sides of the weld as described above. After drying at 80℃ for 15 minutes, AC tungsten inert gas (TIG) welding was performed. The welding current was 100A, the arc voltage was 12V, the welding speed was 160mm / min, the TIG diameter was 3.2mm, and the distance from the TIG tip to the plate surface was 2.0mm. The argon flow rate on the front side was [not specified]. The flow rate was 15 L / min, and the back argon flow rate was 8 L / min. Five welding test plates were prepared for each group. The porosity test was performed using digital X-ray inspection to inspect the entire effective weld of each welding test plate. During the inspection, the image quality meter was placed on the X-ray source side and imaged simultaneously with the weld to ensure that the full width of the weld and the heat-affected zones on both sides were included in the inspection area. The obtained digital X-ray images were grayscale corrected and dimensionally calibrated. After excluding the 10 mm area at the arc initiation end and arc termination end of the weld, the sum of the confirmed porosity projection areas in the effective weld image was divided by the corresponding effective weld projection area and multiplied by 100% to obtain the porosity. The arithmetic mean of the test results of the five test plates was taken.
[0038] For the transverse tensile strength test, one transverse tensile specimen is cut from the middle of each welded test plate that has undergone radiographic inspection, along a direction perpendicular to the weld axis. The specimen axis is perpendicular to the weld axis, and the weld is located at the center of the parallel section of the specimen. The excess height on the front and back of the weld is machined to be flush with the surface of the base material. The surface of the base material must not be damaged during the machining process. The width of the parallel section of the specimen is 12.5 mm, and the original gauge length is 50 mm. Tensile testing is performed using a material testing machine at 23℃±5℃. During the loading process, the specimen is kept under axial force, and the crossbeam displacement speed is 2 mm / min. The loading is continued until the specimen breaks. The transverse tensile strength is calculated based on the original cross-sectional area of the specimen and the maximum test force. At the same time, the fracture location is recorded, and the arithmetic mean of the transverse tensile strength of 5 specimens is taken.
[0039] The weld microhardness test uses cross-sectional specimens after the penetration depth test. After re-grinding and polishing, test lines are set in the middle of the weld thickness direction. The test lines pass sequentially through one side of the base material, the heat-affected zone, the weld center, the other side of the heat-affected zone, and the other side of the base material. Five test points are selected in the weld center area, with a spacing of not less than 0.5 mm between adjacent indentation centers. The Vickers microhardness method is used for testing, with a test force of 1.961 N and a holding time of 10 s. The arithmetic mean of the five test points in the weld center area of each specimen is taken, and the arithmetic mean of the five specimens is calculated as the weld microhardness test result.
[0040] The performance test data above are shown in Table 1.
[0041] Table 1: Performance Test Results ; The test results in Table 1 clearly show that, under the condition that the total fluorine content of the magnesium alloy welding flux prepared in Examples 1-3 was not detected, the weld penetration depth reached 4.66-5.12 mm, the penetration depth to weld width ratio reached 0.70-0.82, the porosity was 0.24-0.39%, the transverse tensile strength was 226-238 MPa, and the weld microhardness was 67.4-71.2 HV0.2; while the weld penetration depth of Comparative Examples 1-3 was only 3.40-4.31 mm, the penetration depth to weld width ratio was 0.48-0.62, the porosity was 0.72-1.45%, the transverse tensile strength was 184-214 MPa, and the weld microhardness was 60.7-65.3 HV0.2.
[0042] Based on the average values of Examples 1-3 and Comparative Examples 1-3, the weld penetration depth of the examples increased from 3.86 mm to 4.87 mm, an increase of approximately 26.1%; the penetration depth to weld width ratio increased from 0.55 to 0.76, an increase of approximately 36.7%; the porosity decreased from 1.04% to 0.31%, a decrease of approximately 70.0%; the transverse tensile strength increased from 201 MPa to 232 MPa, an increase of approximately 15.4%; and the weld microhardness increased from 63.4 HV0.2 to 69.5 HV0.2, an increase of approximately 9.6%. This indicates that the flux can improve the oxide film activation state, molten pool heat transfer state, and weld formation quality in the welding area without using fluorine-containing components.
[0043] Compared with Comparative Example 1, Example 1 showed that the weld penetration depth increased from 3.88 mm to 5.12 mm, the penetration depth to weld width ratio increased from 0.56 to 0.82, the porosity decreased from 0.72% to 0.24%, and the transverse tensile strength increased from 205 MPa to 238 MPa. This indicates that after the zinc chloride-activated lithium calcium sodium composite salt underwent melt composite treatment, the distribution of anhydrous zinc chloride in the multi-component chloride salt was regulated, overcoming the problems of local enrichment and uneven activation that easily occur when anhydrous zinc chloride is directly mixed with other chloride salts. This made the oxide film activation process and the molten salt coverage process more stable.
[0044] Compared with Comparative Example 2, Example 1 showed that the porosity decreased from 0.96% to 0.24%, the transverse tensile strength increased from 214 MPa to 238 MPa, and the weld microhardness increased from 65.3 HV0.2 to 71.2 HV0.2. This indicates that magnesium potassium chloride salt-coated silicon carbide activated micro powder can change the contact and distribution state between green silicon carbide micro powder and the basic fluorine-free composite salt, reduce particle aggregation and uneven local distribution caused by direct mixing of green silicon carbide micro powder, and make the effect of green silicon carbide micro powder in the welding area more uniform. Comparative Example 3, which simultaneously eliminated the molten composite structure of zinc chloride-activated lithium calcium sodium composite salt and the molten salt coating structure of magnesium potassium chloride-coated silicon carbide activated micropowder, showed the lowest weld penetration, penetration-to-width ratio, transverse tensile strength, and weld microhardness, and the highest porosity. This further indicates that zinc chloride-activated lithium calcium sodium composite salt and magnesium potassium chloride-coated silicon carbide activated micropowder have a synergistic effect in oxide film activation, molten salt coating, particle dispersion, and weld pool control.
[0045] Examples 1-3 solve the problems of easy segregation of active components, easy aggregation of particulate components, insufficient activation of oxide film, insufficient weld penetration, many porosity defects, and decreased mechanical properties of joints in existing non-fluorinated chloride salt fluxes.
Claims
1. A fluorine-free flux for welding magnesium alloys, characterized in that, The components include the following parts by weight: Anhydrous potassium chloride 22-30 parts, anhydrous sodium chloride 12-18 parts, anhydrous lithium chloride 10-16 parts, anhydrous calcium chloride 8-14 parts, anhydrous magnesium chloride 10-16 parts, anhydrous potassium bromide 3-6 parts, zinc chloride activated lithium calcium sodium composite salt 8-12 parts, magnesium potassium chloride salt coated silicon carbide activated micro powder 3-6 parts; The preparation method of the zinc chloride activated lithium calcium sodium composite salt includes: A1. By weight, 30-38 parts of anhydrous lithium chloride, 26-34 parts of anhydrous calcium chloride and 18-26 parts of anhydrous sodium chloride are vacuum dried separately, and 8-14 parts of anhydrous zinc chloride are vacuum dried; cooled under nitrogen protection; the dried anhydrous lithium chloride, anhydrous calcium chloride, anhydrous sodium chloride and anhydrous zinc chloride are mixed to obtain a composite salt mixture; A2. Add the composite salt mixture to a covered crucible, heat it to 500-530℃ under nitrogen protection, stir and keep it at the temperature to obtain zinc-containing composite molten salt; cool, crush, grind, vibrate and sieve the zinc-containing composite molten salt, and then vacuum dry it. The preparation method of the magnesium potassium chloride-coated silicon carbide activated micro powder includes: B1. By weight, 45-55 parts of anhydrous magnesium chloride and 25-35 parts of anhydrous potassium chloride are vacuum dried separately, and 15-25 parts of green silicon carbide micro powder are vacuum dried and cooled under nitrogen protection; the dried anhydrous magnesium chloride and anhydrous potassium chloride are added to a covered crucible, heated to 500-550℃ under nitrogen protection, stirred and kept at the temperature to obtain magnesium potassium chloride composite molten salt; B2. Under stirring, the dried green silicon carbide micro powder is added to the magnesium potassium chloride composite molten salt and stirring is continued to obtain the coated molten salt slurry. The coated molten salt slurry is cooled, crushed, ground, vibrated and screened, and then vacuum dried.
2. The fluorine-free flux for magnesium alloy welding according to claim 1, characterized in that, In step A1, anhydrous lithium chloride, anhydrous calcium chloride, and anhydrous sodium chloride are vacuum dried at 180-230℃ for 2-4 hours, and anhydrous zinc chloride is vacuum dried at 120-160℃ for 1.5-3 hours.
3. The fluorine-free flux for magnesium alloy welding according to claim 1, characterized in that, In step A2, the stirring and heat preservation time is 20-40 minutes at 500-530℃.
4. The fluorine-free flux for magnesium alloy welding according to claim 1, characterized in that, In step B1, the stirring and heat preservation time is 20-40 minutes.
5. The fluorine-free flux for magnesium alloy welding according to claim 1, characterized in that, In step B2, the dried green silicon carbide micro powder is added to the magnesium potassium chloride composite molten salt, and the stirring time is continued for 20-40 minutes.
6. A method for preparing a fluorine-free flux for welding magnesium alloys according to any one of claims 1-5, characterized in that, step... include: S1. Dry anhydrous potassium chloride, anhydrous sodium chloride, and anhydrous potassium bromide. Vacuum dry anhydrous lithium chloride, anhydrous calcium chloride, and anhydrous magnesium chloride. After drying, cool under nitrogen protection. Mix the dried anhydrous potassium chloride, anhydrous sodium chloride, anhydrous lithium chloride, anhydrous calcium chloride, anhydrous magnesium chloride, and anhydrous potassium bromide to obtain a basic fluorine-free composite salt. S2. Under stirring, zinc chloride activated lithium calcium sodium composite salt and magnesium potassium chloride salt coated silicon carbide activated micro powder are added to the basic fluorine-free composite salt in sequence and mixed further to obtain flux mixed powder; the flux mixed powder is deagglomerated and vibrated sieve, then vacuum dried and sealed in packaging.
7. The method for preparing the fluorine-free flux for magnesium alloy welding according to claim 6, characterized in that, In step S1, anhydrous potassium chloride, anhydrous sodium chloride, and anhydrous potassium bromide are dried at 180-220℃ for 2-3 hours, and anhydrous lithium chloride, anhydrous calcium chloride, and anhydrous magnesium chloride are vacuum dried at 140-170℃ for 3-5 hours.
8. The method for preparing the fluorine-free flux for magnesium alloy welding according to claim 6, characterized in that, In step S2, the vacuum drying temperature is 120-150℃, and the vacuum drying time is 1-2 hours.
Citation Information
Patent Citations
Soldering flux filled type pulse welding method for magnesium alloy pipe fitting
CN104551355A
Soldering flux for zinc-aluminum-based solder and preparation method thereof
CN110508972A